The Influence of Product Design and Beauty Vlogger Review on Serum Products Purchasing Decisions - Savitri Devi, Ni Luh Putu Ayu; Carla Rettobjaan, Vitalia Fina; Widnyani, Ni Made (West Science Interdisciplinary Studies, 2024)
In Indonesia, facial care has become a daily routine for women. The research was conducted in the city of Denpasar, the center of government, commerce, and culture in Bali, to understand the impact of product design and beauty vlogger review on serum purchase decisions amid increasing competition in the cosmetics industry. The problem formulation is, does product design influence product purchasing decisions? Does the beauty vlogger review affect the product purchase decision? Does product design and beauty vlogger review influence product purchasing decisions? The research method used was quantitatively descriptive, using surveys with research questionnaires, involving 100 respondents to collect data on serum purchase preferences. The research was analyzed using a double linear regression analysis method, then the data was processed using the help of SPSS software version 29. The results of the test on this study showed that the product design significance value is <0,001 < 0,05, the value of the beauty vlogger review significance is <0,001 < 0.05, so based on data analysis that product design and beauty vlogger review have a significant positive influence on the purchase decision of serum products in the City of Denpasar. In conclusion, attractive product design and positive reviews of beauty vloggers are important factors that influence serum purchase decisions, providing important insights for cosmetics companies in designing effective marketing strategies.